Architect Critical Challenges as a Project Manager in Construction Projects: A Case Study - Mohammadreza Yadollahi; Mohammad Mirghasemi; Rosli Mohamad Zin; Bachan Singh (Advances in Civil Engineering)
All construction professionals such as civil, mechanical, and electrical engineers, quantity surveyors, and architects have important roles in the construction process. Among these, architects are frequently appointed as a project manager (PM). The role of a PM will drive the success of the projects implementation. Therefore, the capability of an architect as a PM (ArPM) is critical in reducing challenges encountered. Accordingly, the identification of these challenges is an important task in selecting an appropriate ArPM. The aim of this study is to identify the most critical challenges faced by an ArPM for construction projects. The data were collected through questionnaires and interviews with architects and professionals in the Malaysian construction industry. Because of the fuzziness and uncertainty of subjective responses, Fuzzy Set Ttheory is applied to identify critical challenges. A total of 65 questionnaires were distributed and 36 questionnaires were returned. The results revealed that the critical challenges faced by an ArPM are “poor planning,” “unfamiliar technology,” “unfamiliarity with green buildings and materials,” “inappropriate scheduling,” and “poor workmanship.” All critical challenges were then categorized into six main groups including technical, managerial, personal skills, contractual, psychological, and financial.